STUDI BIAYA WAKTU PEMAKAIAN ALAT BERAT PADA PERBAIKAN PERKERASAN PONDASI BAWAH (SUB BASE COURSE) RUAS JALAN KM.38 SEMOI SEPAKU PROVINSI KALIMANTAN TIMUR - WAHYUDINNUR, WAHYUDINNUR (KURVA S JURNAL MAHASISWA, 2020)
The use of heavy equipment is very important in a road job. In the process of analyzing the feasibility of the work carried out in-depth studies of various aspects such as the technical aspects, the environment, human and weather. This thesis will discuss the study of the cost of time to use heavy equipment on the improvement of the sub base course (sub base course) km.38 Semoi Sepaku in East Kalimantan, in terms of the tool to be used, the number of tool that will be used, the composition of the tool, and the cost of the tools at this work. The purpose and purpose of writing this final project is to find out or explain the calculation of the types of heavy tools used and operational costs for the basic unit price of wages, tool materials and implementation time. From the results of the calculation of the budget plan The results obtained in the budget plan (RAB) are Rp. 1,566,868,198.91. 10% PPN Rp. 156,686,819.89. The amount includes PPN as a whole Rp. 1,723,555,018,80. With the details of the ordinary excavation work Rp. 21,725,055.89, aggregate foundation class B Rp. 383,386,314.85 and drainage layers work Rp. 1,161.756,828,17. with the quantity and volume of each work that is ordinary excavation 680.26 m3 , aggregate foundation layer B class 680.26 m3 , drainage layer work 1857.64 m3 .